Update on treating canine staphylococcal skin infections. (24th January 2014) - Nuttall, Tim
Abstract : The use of antimicrobials in veterinary practice has become a controversial issue and responsible use of such medicines is encouraged throughout the profession. This article highlights the advances in treating staphylococcal skin infections that are most relevant to general practitioners and explains how to prescribe responsibly when treating these conditions.